Ditelureto de difenila induz prejuízos no desenvolvimento, neurotoxicidade e desmielinização no sistema nervoso central de filhotes de ratos wistar - Pinton, Simone (2009)
The purpose of this study was to investigate if myelinogenesis is related to the mechanism by which diphenyl ditelluride [(PhTe)2] causes toxicity in rat pups. The present study was performed to examine whether the behavioral performance is related to demyelination process induced by (PhTe)2 in rat pups. acetilcholinesterase (AChE) activity was carried out in cerebral cortex of rat pups since studies have demonstrated that demyelinating events interfere with the activity of this enzyme. Rat pups received a single subcutaneous injection of (PhTe)2 (0,25 μmol/kg) or vehicle (canola oil) at 14th post natal day (PND). From day 1 to 7 (PND 15 to 21) after exposure, negative geotaxis, forelimb support and open field tests were performed in pups. Rat pups were euthanized daily (from day 1 to 7) immediately after the behavioral tests. The cerebral density of myelin and histological analysis were performed. The appearance of classic signs of toxicity, behavioral alterations and demyelination of CNS was dependent of the time after (PhTe)2 exposure to rat pups. Neuronal damage, revealed by histological analysis, and the increase in AChE activity occurred at 4th and 5th day after (PhTe)2 exposure, which is coincident with the critical period of demyelination. In conclusion, exposure to (PhTe)2 induced an impairment of developmental behavioral, neurotoxicity and demyelination in the central nervous system of rat pups.